2023
DOI: 10.1097/dss.0000000000003738
|View full text |Cite
|
Sign up to set email alerts
|

Dermabrasion Versus Microneedling in Transplantation of Autologous Noncultured Melanocyte–Keratinocyte Cell Suspension in Patients With Vitiligo

Abstract: BACKGROUNDAutologous noncultured melanocyte–keratinocyte transplantation is one of the procedures used to treat stable vitiligo with varying reported results. Recipient site preparation is one of the variables that could affect repigmentation outcomes.OBJECTIVETo assess the effectiveness of transplanting autologous melanocyte–keratinocyte suspension in patients with stable vitiligo and to compare recipient site preparation using dermabrasion versus microneedling.METHODSFrom March 2020 to September 2022, this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…One group had a recipient site treated with FCO 2 laser ablation (fractional group), while the other group had a recipient site treated with full surface CO 2 laser ablation (full ablation group) In the study, using FCO 2 laser resulted in excellent repigmentation in 40% of cases, good repigmentation in 35% of cases, and poor repigmentation in 25% of cases. On the other hand, the full surface CO 2 laser exhibited excellent repigmentation in 35% of cases and good repigmentation in 30% of cases, while fair repigmentation was seen in 10% to 50% of cases and poor results in 10% to 25% of cases Depigmentation at the donor site Hasan et al [ 47 ] RCT 40 patients Unknown Unknown vitiligo Transplantation of autologous epidermal melanocyte/keratinocyte cells The participants were divided into two categories: group A underwent dermabrasion for recipient site preparation, while group B received microneedling. After a period of three months, the patients were evaluated to determine the level of repigmentation Both dermabrasion and microneedling were effective in achieving repigmentation in the patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One group had a recipient site treated with FCO 2 laser ablation (fractional group), while the other group had a recipient site treated with full surface CO 2 laser ablation (full ablation group) In the study, using FCO 2 laser resulted in excellent repigmentation in 40% of cases, good repigmentation in 35% of cases, and poor repigmentation in 25% of cases. On the other hand, the full surface CO 2 laser exhibited excellent repigmentation in 35% of cases and good repigmentation in 30% of cases, while fair repigmentation was seen in 10% to 50% of cases and poor results in 10% to 25% of cases Depigmentation at the donor site Hasan et al [ 47 ] RCT 40 patients Unknown Unknown vitiligo Transplantation of autologous epidermal melanocyte/keratinocyte cells The participants were divided into two categories: group A underwent dermabrasion for recipient site preparation, while group B received microneedling. After a period of three months, the patients were evaluated to determine the level of repigmentation Both dermabrasion and microneedling were effective in achieving repigmentation in the patients.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the comparison of the two methods of dermabrasion and microneedling at the transplant site, both methods have shown effectiveness. However, dermabrasion has demonstrated significant improvement compared to microneedling [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chen 58 found surgical intervention to be effective for treating stable vitiligo, with positive results from both noncultured and cultured epidermal cell suspensions. Studies 59,60 found that repigmentation after autologous epidermal cell suspensions remained stable in most treated patches. Dev et al 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Chen 58 found surgical intervention to be effective for treating stable vitiligo, with positive results from both noncultured and cultured epidermal cell suspensions. Studies 59,60 found that repigmentation after autologous epidermal cell suspensions remained stable in most treated patches. Dev et al 61 posited that the preparation of recipient sites using manual dermabrasion (MD) or electrofulguration-assisted dermabrasion influenced repigmentation rates.…”
Section: F I G U R Ementioning
confidence: 99%